PRESSURES AND IMPACTS ON THE MENTAL HEALTH OF NURSING STUDENTS: A SYSTEMATIC REVIEW (CIPEEX, 2025)
Introduction: Universities play a crucial role in educating citizens committed to social transformation and the promotion of individual and collective rights. Health, defined by the WHO as a state of complete physical, mental, and social well-being, should be a priority within educational institutions. Mental health, in turn, is essential for individuals to develop their skills and contribute positively to the community. Objective: The specific objective of this study was to analyze the influence of identity on the reframing of the demands of nursing students' lives in mental health. Methodology: The systematic review identified nine relevant articles on the mental health of nursing students, revealing a high prevalence of anxiety and depressive symptoms. Results: The analysis of these studies highlighted the urgent need for interventions to support students' mental health. Conclusion: The importance of therapies and coping strategies to reduce the prevalence of these problems and improve the well-being of students is understood.
Keywords: nursing; academics; mental health; university